Assessment of Climatic Guidelines and Urban Planning in North-Eastern Coast of Brazil - Anjos, Max (2021)
Incorporating scientific knowledge of climate into urban planning is a major challenge for the healthy growth of a city. This chapter presents a proposal for planning local climate action based on urban climatic maps (UCMaps). The UCMaps are an accessible and easy support tool for planners, architects, and local government to make the right decision in the planning process. Based on the UCMaps, we recommend a set of climatic guidelines to combat the phenomenon of the Urban Heat Island in a city located on the northeast coast of Brazil. These maps identify the key climate areas in terms of UHI behaviour and excess heat stress based on climatopoes, which are areas of “special local climates” or “potential climate response” influenced by the urban morphology, land use and ventilation conditions. The relationship between UCMaps and Master Plan is also presented. With the UCMap, urban policymakers have various urbanistic interventions, measures, and strategies available to combat the adverse effects of the UHI and preserve the climate-related ecosystem services.